Síntese pelo método pechini e caracterização da zircônia dopada com cério e neodímio - Andrade, Izangela Marculino de (2012)
In this study five compositions were synthesized zirconia doped with cerium and neodymium ions in the system Ce10-xNdx Zr90O2 with 0,5 ≤ x ≤ 4,0 using the Pechini method. The powders were characterized by thermogravimetric analysis, differential thermal analysis, infrared spectroscopy and X-ray diffraction, with application of Rietveld refinement of the calcination temperatures of 350ºC/3h and 30 minutes at 900ºC/3h. All compositions stabilized with a mixture of cubic and tetragonal phase zirconia. The samples were pressed into bars and sintered at 1500°C/3h and 1500°C/6h, being characterized by Xray diffraction, with application of the Rietveld refinement, density and porosity using Archimedes method, scanning electron microscopy and resistance the three point bending. It has been observed the increase in strength with increasing sintering temperature for the compositions x = 2,0 and x = 4,0. For x = 2,0 the main phase was the cubic with 92,56% with crystallite size of 0,56 μm, density and porosity of 96,82% from 1,36%. For x = 4,0 was a mixture of cubic and tetragonal phase with 21% and 37,98%, respectively. The crystallite size was 54,21 nm and 49,64 nm with a density porosity of 97,45% and 1,32% respectively. In the analysis of the fracture surface was observed a greater amount of grain fracture intragranular type, which contribute to increase the mechanical strength of the ceramic. Increased addition of the neodymium ion in the crystal lattice of the zirconium showed a nearly linear behavior with increasing mechanical strength of the zirconia ceramic. Was obtained a bending resistance of 537 ± 38 MPa for the composition x = 2,0 predominantly attributed to cubic phase with 92,56%